Shape selective synthesis of long-chain linear alkyl benzene (LAB) with AIMCM-41/beta zeolite composite catalyst - Bordoloi, Ankur; Devassy, Biju M.; Niphadkar, P. S.; Joshi, P. N.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2006)
The liquid-phase alkylation of benzene with long-chain olefins such as 1-decene, 1-octene and 1-dodecene was carried out over AIMCM-41/Beta zeolite composite material as catalyst. The catalyst was prepared by seeding method and characterized by XRD, N-2 sorption, FTIR pyridine adsorption, NH3-TPD and SEM. Powder XRD of AlMCM-41/Beta zeolite composite material showed the co-existence of well-structured microporous and mesophase of AlMCM-41. The typical textural characteristics of micro- and meso-structured phases were observed in the composite material. The effect of temperature, reactant molar ratios and catalyst weight on 1-dodecene conversion and products selectivity was studied. The composite catalyst was found to be the highly selective towards the formation 2-dodecylbenzene. Under the reaction conditions of 120 degrees C, benzene/1-dodecene molar ratio 10 and time 2h, the catalyst gave 48% dodecene conversion with 76%, 2-dodecylbenzene selectivity. Significant improvement in catalytic activity has been achieved by composite material as compared to Al-MCM-41. Although zeolite beta and composite material gave similar conversion of dodecene, the composite material showed higher selectivity towards 2-dodecylbenzene, which could be due to higher diffusibility of 2-dodecylbenzene isomer in the composite material. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: AIMCM-41/beta zeolite composite; Alkylation; Benzene; long-chain olefins

One-step synthesis of SBA-15 containing tungsten oxide nanoclusters: a chemoselective catalyst for oxidation of sulfides to sulfoxides under ambient conditions - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Chemical Communications, 2007)
Tungsten oxide nanoclusters supported highly ordered mesoporous SBA-15 material has been successfully synthesized in a single step using a non-ionic surfactant as a template and used for the selective oxidation of sulfur compounds, giving excellent yields at room temperature with exceptional catalyst recyclability.

Organotin-oxometalate coordination polymer catalyzed oxyfunctionalization of monoterpenes - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2007)
Keywords: Heck reaction; kinetics; Palladacycle

Oxyfunctionalisation of adamantane using inorganic-organic hybrid materials based on isopoly and heteropoly anions: kinetics and mechanistic studies - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2007)
{Oxyfunctionalisation of adamantane with 30% aq.H2O2 in butyronitrile solvent was efficiently catalyzed by inorganic-organic hybrid materials synthesized by the immobilisation of isopoly (WOx = sodium tungstate
Keywords: adamantane; inorganic-organic hybrid materials; oxyfunctionalisation; vanadium (V) superoxo intermediate

Selective oxidation of anthracene using inorganic-organic hybrid materials based on molybdovanadophosphoric acids - Bordoloi, Ankur; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2007)
{Inorganic-organic hybrid materials were synthesized by immobilization of molybdovanadophosphoric acids onto mesoporous silicas, such as MCM-41, MCM-48, and SBA-15, through an organic linker. 12-Molybdovanadophosphoric acids of the general formula H3+xPMO12-xVxO40 (x = 0-3).nH(2)O, such as H-4[
Keywords: EPDM; Photostabilization; polymeric HALS

Heteropoly acid-based supported ionic liquid-phase catalyst for the selective oxidation of alcohols - Bordoloi, Ankur; Sahoo, Suman; Lefebvre, F.; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A supported ionic liquid strategy has been applied for the immobilization of a heteropolyacid, molybdovanadophosphoric acid, onto ionic liquid-modified mesoporous silica SBA-15. The immobilized catalyst demonstrated high activity in the aerobic oxidation of primary and secondary alcohols to aldehydes and ketones, respectively. No overoxidation of the primary alcohols to carboxylic acids was observed. Secondary alcohols were chemoselectively oxidized to ketones in the presence of primary alcohol, hetero atom, and allyl groups. This catalyst could be recycled five times without obvious loss of activity. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Air as an oxidant; Mesoporous silica SBA-15; Molybdovanadophosphoric acid; Selective oxidation; Supported ionic liquid

Inorganic-organic hybrid materials based on functionalized silica and carbon: a comprehensive understanding toward the structural property and catalytic activity difference over mesoporous silica and carbon supports - Bordoloi, Ankur; Mathew, Nevin T.; Lefebvre, F.; Halligudi, Shivaraj B. (Microporous and Mesoporous Materials, 2008)
Inorganic-organic hybrid materials based on functionalized silica and carbon were synthesized by anchoring molybdovanadophosphoric acid (H-5[PMo10V2O40]center dot 32.5H(2)O) onto amine-functionalized SBA-15, ethane-bridged SBA-15 and mesoporous carbon, respectively. Small angle X-ray diffraction, N-2 sorption analysis, HRTEM, SEM, IFT-IR, CP-MAS NMR were used to diagnose the mesoporous structure of inorganic-organic hybrid materials. The structural integrity of molybdovanadophosphoric acid has been found to be retained after immobilization over mesoporous materials. These inorganic-organic hybrid materials were tested in the environmentally friendly oxidation of 2-methylnaphthalene (2MN) with 30%, aqueous hydrogen peroxide. Molybdovanadophosphoric acid containing mesoporous organosilica hybrid material (ethane-bridged SBA-15) exhibited higher catalytic activities in the oxidation of 2MN to give a clean product 2-methy-1,4-naphthoquinone (menadione vitamin K3 precursor), because of the improved hydrophobicity of the material. The correlation between structural properties and catalytic activities of these hybrid materials has been well addressed in our present studies. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: 2-Methylnaphthalene; inorganic-organic hybrid materials; mesoporous carbon; mesoporous organosilica; Oxidation

[Ru(salen)(NO)] complex encapsulated in mesoporous SBA-16 as catalyst for hydrogenation of ketones - Bordoloi, Ankur; Amrute, Amol P.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
SBA-16 mesoporous silica with cubic lm3m structure was synthesized using Pluronic F127 poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (EO106PO70EO106) and it blends with Pluronic P123 triblock copolymer (EO20PO70EO20) as supramolecular templates. The resulting material was used for encapsulating [Ru(salen)(NO)] complex and used in the hydrogenation of ketones to the corresponding alcohols. The pore entrance size of SBA-16 was precisely tailored by silylation with diphenyldichlorosilane to trap [Ru(salen)(NO)] complex in the cage of SBA-16. Small angle XRD, N-2 sorption measurements, UV-Vis and FT-IR analysis evidences the structural integrity of mesoporous silica as well as the complex. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Encapsulation; Hydrogenation; Ketones; SBA-16; [Ru(salen)(NO)] complex

Sol-gel synthesis of MoO(3)/SiO(2) composite for catalytic application in condensation of anisole with paraformaldehyde - Amrute, Amol P.; Bordoloi, Ankur; Lucas, Nishita; Palraj, K.; Halligudi, Shivaraj B. (Catalysis Letters, 2008)
MoO(3)/SiO(2) composite with varying amounts of MoO(3) loading (1-20 wt.%) were prepared by sol-gel method and calcined at 500 C. These catalysts were employed for the liquid phase condensation of anisole with paraformaldehyde. All the catalysts were characterized by N(2) sorption, XRD, and NH(3)-TPD. The activities of synthesized MoO(3)/SiO(2) catalysts were compared with p-toluene sulfonic acid (p-TSA), the most frequently used catalyst for the condensation reactions, and with a supported metal oxide (WO (x) /ZrO(2)). Under the similar reaction conditions, synthesized 10 wt.% MoO(3)/SiO(2) catalyst calcined at 500 C was found to be the most active in the condensation of anisole with paraformaldehyde.
Keywords: 4; 4'-Dimethoxydiphenylmethane; Condensation of anisole; MoO(3)/SiO(2) composites; Paraformaldehyde; Sol-gel synthesis

Studies in structural characterization and correlation with the catalytic activity of an efficient and stable WOx/SBA-15 nanocomposite catalyst - Bordoloi, Ankur; Halligudi, Shivaraj B. (Journal of Catalysis, 2008)
A new WOx/SBA-15 nanocomposite catalyst system was developed by hydrothermal synthesis. The material was characterized by X-ray diffraction, high-resolution transmission electron microscopy, sorption analysis, FT-IR, CP-MAS NMR, XPS, and energy-dispersive X-ray analysis. Various types of aromatic and aliphatic sulfides were selectively oxidized to sulfoxides in good to excellent yields without becoming overoxidized to the sulfones using 70% aq. tert-butyl hydrogen peroxide in the presence of nanocomposite catalyst at room temperature. The catalyst could be easily recovered and reused for at least eight reaction cycles under the reaction conditions described here with no significant loss of reactivity. (c) 2008 Elsevier Inc. All rights reserved.
Keywords: catalytic oxidation; mesoporous materials; Sulfides; Sulfoxides; tungsten oxide nanocluster

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Mesoporous silica immobilized cobalt complex: an efficient catalyst for epoxides ring opening by aromatic amines under ambient conditions - Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shivaraj B. (Catalysis Communications, 2009)
{Cobalt complex, CobpbH(2)Cl(2)2H(2)O [where
Keywords: beta-Amino alcohols; CobpbH(2)Cl(2)2H(2)O complex; Epoxide ring opening; Immobilization; SBA-15

MoO3/SiO2: an efficient and selective catalyst for the synthesis 1,3-dioxolane and 1,3-dioxane - Amrute, Amol P.; Sahoo, Suman; Bordoloi, Ankur; Hwang, Young Kyu; Hwang, Jin-Soo; Halligudi, Shiva B. (Catalysis Communications, 2009)
A series of MoO3/SiO2 catalysts with varying amounts of MoO3 has been synthesized and the catalytic activities of these were compared with the known solid acid catalysts in the synthesis of 1,3-dioxolane. MoO3/SiO2 catalyst showed a better activity and selectivity in 1,3-dioxolane synthesis compared to the other catalysts. MoO3/SiO2 catalyst system was further successfully applied for the synthesis of 1,3-dioxanes in the Prins cyclization of olefins and formaldehyde. The proposed catalyst was thermally stable and could be recovered and reused at least in four consecutive cycles with no significant loss in the substrates conversions and products selectivities. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 1; 3-Dioxolanes; Cycloaddition; MoO3/SiO2; Prins cyclization; Sol-gel method; solid acid catalysts

Ordered mesoporous silica as supports in the heterogeneous asymmetric catalysis - Sahoo, Suman; Bordoloi, Ankur; Halligudi, Shivaraj B. (Catalysis Surveys from Asia, 2011)
Enantioselective synthesis of organic compounds has been studied by homogeneous catalysts for several years. However, these catalysts have yet to make a significant impact on industrial scales for fine chemical synthesis. A primary reason is the designing of a homogeneous asymmetric catalyst, which requires relatively bulky ligands and catalyst recovery and recycling often causes problems. One of the convincing ways to overcome this problem is to immobilise the asymmetric catalyst onto a solid support and the resulting heterogeneous asymmetric catalyst system can, in principle, be readily re-used. A large number of supports such as inorganic oxides including zeolites, alumina, zirconia, silica and organic polymers have been employed as supports in heterogeneous asymmetric catalysis. Therefore, in this review article we have summarized the work done by us in our laboratory on the immobilization of chiral transition metal complexes such as Ru, Ir, Mn and Ti onto ordered mesoporous silica and its asymmetric catalysis. All these immobilized catalysts were well characterized by different physicochemical techniques to confirm the structural retention of the support as well as the active metal complex after immobilization. This report includes our asymmetric catalytic investigations in enantioselective reactions such as hydrogenation of ketones, olefins, oxidation of sulfides and oxidative kinetic resolution of alcohols and sulfoxides through immobilized heterogeneous catalyst systems.
Keywords: Enantioselective hydrogenation; Enantioselective oxidation; Immobilization; Mesoporous silica; Oxidative kinetic resolution

Acid-base cooperative catalysis over mesoporous nitrogen-rich carbon - Goyal, Reena; Sarkar, Bipul; Lucas, Nishita; Bordoloi, Ankur (ChemCatChem, 2014)
WOx nanoclusters (2-3 nm) embedded on a mesoporous nitrogen-rich carbon material were synthesized by using novel methodology. This material was very effectively capitalized as a new carbon-based acid-base cooperative catalyst for sequential acetal hydrolysis and Knoevenagel condensation reactions. The protocol was also explored for the nitroaldol condensation reaction.
Keywords: cooperative catalysts; Knoevenagel condensation; mesoporous materials; Nanostructures; nitro aldol reaction

Studies of synergy between metal-support interfaces and selective hydrogenation of HMF to DMF in water - Goyal, Reena; Sarkar, Bipul; Bag, Arijit; Siddiqui, Nazia; Dumbre, Deepa K.; Lucas, Nishita; Bhargava, Suresh Kumar; Bordoloi, Ankur (Journal of Catalysis, 2016)
Metal-support interfaces play a very important role in heterogeneous catalysis. The interfacial interactions not only are responsible for stabilizing the necessary oxidation state to facilitate the reaction but also enhance the stability of the catalyst system. Nano dispersion of Ni on mesoporous nitrogen-rich carbon material has been achieved using two different synthesis methods. It was observed that nickel (0) gets stabilized by strong interfacial interaction with the nitrogen atoms of the support material, and the material was found to be very economic and efficient for the conversion of HMF to DMF in aqueous medium. The material shows >= 99% conversion to 5-(hydroxymethyl) furfural (HMF) within 6 h of reaction with 98.7% DMF selectivity. A unique correlation between synthesis methods and particle sizes with catalytic performance has been observed for these newly developed materials. Furthermore, a DFT calculation has been performed to predict the reaction mechanism. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: biofuels; Biomass; Hydrogenation; mesoporous carbon; Ni-CNx

Facile synthesis of Al2O3-Pt nanocomposite and its catalytic activity - Das, Subhasis; Bordoloi, Ankur; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S.; Bala, Tanushree (Materials Research Express, 2017)
Pt nanoparticles were synthesized on gamma-alumina support in presence of oleic acid which was found to prevent clustering of Pt nanoparticles on the support. Various percentage of Pt loading on the alumina changed the catalytic activity for preferential oxidation of CO at relatively low temperature in H-2 rich stream. Pt nanoparticles when synthesized in absence of oleic acid, were all clustered and did not have any catalytic activity. The presence of oleic acid promoted stability preventing agglomeration of Pt nanoparticles. The catalyst thus prepared was characterized thoroughly and their catalytic activity was studied in details.

Multiple functionalities of Ni nanoparticles embedded in carboxymethyl guar gum polymer: catalytic activity and superparamagnetism - Sardar, Debasmita; Sengupta, Manideepa; Bordoloi, Ankur; Ahmed, Md. A.; Neogi, S. K.; Bandyopadhyay, Sanjoy; Jain, Ruchi; Gopinath, Chinnakonda S.; Bala, Tanushree (Applied Surface Science, 2017)
Composites comprising of metallic nanoparticles in polymer matrices have allured significant importance due to multifunctionalities. Here a simple protocol has been described to embed Ni nanoparticles in carboxymethyl guar gum (CMGG) polymer. The composite formation helps in the stabilization of Ni nanoparticles which are otherwise prone towards aerial oxidation. Further the nanoparticles retain their superparamagnetic nature and catalytic capacity. Ni-Polymer composite catalyses the reduction of 4-Nitrophenol to 4-Aminophenol very efficiently in presence of NaBH4, attaining a complete conversion under some experimental conditions. Ni-Polymer composite is well characterized using UV–vis spectroscopy, FTIR, XPS, powder XRD, TGA, SEM and TEM. A detailed magnetic measurement using superconducting quantum interference device-vibrating sample magnetometer (SQUID-VSM) reveals superparamagnetic behaviour of the composite.

In-situ experimental and computational approach to investigate the nature of active site in low-temperature CO-PROX over CuOx-CeO2 catalyst - Adak, Shubhadeep; Rabeah, Jabor; Ranjan, Ravi; Khan, Tuhin Suvra; Poddar, Mukesh Kumar; Gupta, Rishi Kumar; Sasaki, Takehiko; Kumar, Sagar; Bordoloi, Ankur; Gopinath, Chinnakonda S.; Bruckner, Angelika; Bal, Rajaram (Applied Catalysis A-General, 2021)
Preferential oxidation (PROX) of carbon monoxide (CO) in presence of excess hydrogen is a necessity to prevent poisoning of the Pt-anode by CO in PEMFCs (Polymer Electrolyte Membrane Fuel Cell). A highly active catalyst, 5 wt% Cu-CeO2 showed 100 % CO conversion at 65 degrees C without any undesirable oxidation of H-2. The catalyst showed no deactivation even after 100 h on stream, making it viable for practical fuel cell application. Operando EPR in the PROX reaction condition revealed highly dispersed mixed valent cations with oxygen vacancies, responsible for the low-temperature PROX activity. At the active site, both Cu and Ce ions were shown to reversibly change their valence states to facilitate the abstraction of bridging lattice oxygen for CO oxidation to CO2. This surface oxygen mediated CO oxidation was found to be much faster than that of H-2 to H2O, which could explain the complete selectivity of oxygen for CO2 formation.
Keywords: CuOx-CeO2; interface; Oxygen vacancy; PROX; Synergistic

Essentials of Mo+6/Mo+4 and Ce+4/Ce+3 redox couples in auto-regenerated catalyst for dry methane reforming - Panda, Satyajit; Singh, Gaje; Kaishyop, Jyotishman; Gazi, Md Jahiruddin; Mule, Harshada Mahadev; Khan, Tuhin Suvra; Sharma, Ojasvi; Bordoloi, Ankur (Chemical Engineering Journal, 2025)
Biogas is a potential renewable carbon resource, and dry reforming is one of the promising routes to mitigate via generating syngas, used as a building block for the synthesis of chemicals and fuels. Coke deposition and metal sintering of the reported catalyst systems are the major challenges to developing an economically feasible dry reforming process. Molybdenum oxide is a versatile material with properties like oxygen storage, oxygen mobility, and sulphur tolerance. Here, an oxygen storage capacity enhanced catalyst has been designed by applying a mono layer molybdenum oxide on ceria-magnesia-modified alumina support using a unique chemical vapor deposition method. The Ru and Ni used as active components, and Gd as a promoter were dispersed over the modified support via a precipitation-deposition approach. The most efficient composition is found to be 4 % Ni, 0.5 % Gd, and 0.5 % Ru with Mo-promoted modified alumina with excellent stability up to 500 h for dry reforming reaction studies. Two redox cycles (Mo+6 to Mo+4 & Ce+4 to Ce+3) facilitated a significant number of oxygen vacancies, to limit surface carbon accumulation and support high catalytic stability and activity. The possible reaction pathways and stable surface intermediates were identified by using in-situ DRIFT studies, which included metal carbonyls, carboxylate species, and surface hydroxyl groups. Moreover, the DRIFT studies were supported with CH4-TPSR analysis and DFT studies evidence the formation of CHx species and subsequent oxidation. The additional advantage of the usage of molybdenum is the excellent S-tolerance capacity, which is fully scrutinized experimentally as well as theoretically.
Keywords: and Methane reforming; Coke resistant; Oxygen storage; Redox couple cycles; Sulphur tolerance